A dynamic systems approach to joint attention in an infant-toddler early childhood centre. (February 2022) - Jacobson, Sarah; Degotardi, Sheila
Abstract: Educator-infant joint attention is widely regarded as important for learning and language development. The shared experience of an object or activity allows infants to extend their thinking and refine their understanding within the context of a collaborative social interaction. Yet most research to date has focused on how the educator establishes and maintains joint attention. Questions as to how an infant and educator coordinate attention and engagement in a distractible group environment have been overlooked, as has the active role the infant plays in this process. This paper uses a dynamic systems approach to study joint attention episodes as they arise during free play within the context of an infant early childhood education and care centre. Using State Space Grids, we operationalise joint attention as co-regulated attentional shifts and demonstrate that it emerges as a moment-to-moment unfolding process from the mutual contributions of both educator and infant. Findings demonstrate that both infants and educators actively seek to engage in joint attention, there are multiple pathways into these episodes, and distractions are common. Importantly, both infant and educator appear motivated and resilient enough to remain engaged despite distractions, demonstrating that joint attention can be successfully established and sustained in this setting.